Tindjauan atas Masalah Hubungan Kerdja Praktis dan Pendidikan Kesardjanaan pada Bagian Mesin Institut Teknologi Bandung - M. Aroef (Journal of Mathematical and Fundamental Sciences, 1963)
Tulisan ini dibuat bersandarkan dasar fikiran jang dianut pada Bagian Mesin I.T.B. dalam mentugaskan para mahasiswanja mendjalankan kerdja praktis diberbagai perusahaan industry Indonesia. Kerdja praktis ini adalah dalam rangka pengisiskan para tjalon sardjana teknik mesin jang dinjatakan dalam rentjana peladjarannja. Bahan2 dikumpulkan berdasarkan pertjakapan2 dengan berbagai pihak dalam soal ini selama djangka waktu penulis mendjadi pengurus kerdja praktis pada Bagian Mesin tersebut. Bahan2 pembahasan akan dibagi kedalam golongan2 tindjauan berikut :* Hubungan kerdja praktis dengan pendidikan mahasiswa* Kerdja praktis sebagai penghubung I.T.B. dengan dunia perusahaan.* Kerdja praktis sebagai djalan bagi dunia industri untuk mengenal mahasiswa2 I.T.B. This article reviews the significance of the practical engineering work experience given by the various industries and workshops in Indonesia to the students of Bandung Institute of Technology, especially related to the mechanical engineering education. This review looks upon the problem utilizing the interest of the parties involved as the bases, namely:the interest of the education of the mechanical engineer to bethe interest of Bandung Institute of Technology as an institute of higher engineering learningthe interest of industrial enterprises.It is endeavored to express the viewpoints as clearly as possible  in agreement with the many statements and opinions conceived by the author during many discussion with various parties about this practical engineering  work experience of the mechanical engineering students of Bandung Institute of Technology. The parts of this article concerning these statements and opinions are presented based on memory, and therefore this article is far from being all inclusive. The author is of the opinion that the most important aspects are sufficiently covered in this short article.